Detection and quantitation of PS20, a phosphorothioate oligodeoxynucleotides in monkey plasma - SHANG Ming-mei; SONG Hai-feng; LIU Xiu-wen; TANG Zhong-ming (Acta Pharmacologica Sinica, 2016)
AIM: To establish the method for quantitation of the phosphorothioate oligodeoxynucleotides (S-ODNs) in plasma. METHODS: Two solid-phase extraction columns combined with a strong anion-exchange column were utilized to remove proteins and lipids in plasma, and the salts were removed by a reverse-phase column followed by dialysis with a 2500 Da-cutoff membrane. The concentration of the tested S-ODNs, PS20, and its metabolites extracted from the plasma were determined by the method of non-gel sieving capillary electrophoresis (NGCE) with diode array detection in the presence of internal standard (IS). RESULTS: The method was with good base number specificity. Relative standard deviation % of both intra and inter assay were all less than 10 %, and the total mean recovery was about 91 %. The methodology was successfully used to determine the PK behavior of an anti-tumor antisense S-ODNs in monkeys and identify the metabolites with single base difference. CONCLUSION: The combined method of solid-phase extraction and NGCE could be used to study the pharmacokinetics of S-ODNs, and the main parameters of the methodology met the requirement of PK study.